2011
DOI: 10.1007/s00018-011-0704-8
|View full text |Cite
|
Sign up to set email alerts
|

Vγ9Vδ2 T cell-based immunotherapy in hematological malignancies: from bench to bedside

Abstract: Many hematological malignancies consist of tumor cells that are spontaneously recognized and killed by Vγ9Vδ2 T cells. These tumor cells generate high amounts of intracellular phosphorylated metabolites mimicking the natural ligands and display a wide range of stress-induced self-ligands that are recognized by Vγ9Vδ2 T cells via TCR-dependent and TCR-independent mechanisms. The intrinsic features of Vγ9Vδ2 T cells and that of tumor cells of hematological origin constitute an ideal combination from which to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 90 publications
(115 reference statements)
0
45
0
Order By: Relevance
“…New approaches including the development of immunotherapy strategies are being actively investigated that may improve outcomes in AHSCT. Innate immune cells, notably NK cells and gd T cells, are of particular interest on account of their ability to kill hematological 2,3 or solid tumor cells 4 without inducing GvHD. 5,6 The anti-leukemic role of gd T cells was suggested by a correlation between Vd1 T cells expansion and prognosis following AHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…New approaches including the development of immunotherapy strategies are being actively investigated that may improve outcomes in AHSCT. Innate immune cells, notably NK cells and gd T cells, are of particular interest on account of their ability to kill hematological 2,3 or solid tumor cells 4 without inducing GvHD. 5,6 The anti-leukemic role of gd T cells was suggested by a correlation between Vd1 T cells expansion and prognosis following AHSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] ␥9␦2T cells are promising as an innate cell population for this purpose because they are usually observed at high frequencies in the human peripheral blood and provide a strong antitumor reactivity against various solid and hematologic cancers. 5 However, within ␥9␦2T-cell populations, individual clones display great diversity in the repertoire because of the activating or inhibitory receptors expressed. 6 Selecting innate cell products for certain cell types, such as those with a low level of inhibitory receptors, therefore seems plausible, especially considering the limited efficacy of adoptively transferred innate immune cells in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…␥9␦2T cells also possess a rearranged TCR that mediates recognition. The phosphoantigen isopentenyl pyrophosphate (IPP) has been suggested to be a key player in ␥9␦2TCR-mediated activation, 5,10,11 but no direct interaction between a ␥9␦2TCR and IPP or any other phosphoantigen has ever been demonstrated. It was previously suggested that positively charged residues within the ␥9␦2TCR are crucial for the response to negatively charged phosphoantigens 12,13 and a potential IPP-binding groove has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its pharmacological effects, zoledronate has immune modulatory activities that include stimulation of proliferation and activation of the V9V2 subset of T cells. T cells expressing the V9V2 T cell receptor play a significant role in immune surveillance and defense [333][334][335]. These cells have the ability to recognize and kill tumor cells in an MHC-independent manner, suggesting their potential utility in the elimination of cancer cells with poor antigen presentation capacity [336].…”
Section: Bisphosphonatesmentioning
confidence: 99%